Organs of BALB/c mice can be injured in course of tularemia - Pavlis, Oto; Kusakova, Eva; Novotny, Ladislav; Pohanka, Miroslav (Biomedical papers, 2014)
Background: Francisella tularensis is a biological agent exploitable for bioterrorism and biological warfare purposes due to serious pathogenic progression and easy dissemination. Despite intensive research in the past, some adverse consequences remain unclear. One consequence of this pathogen is oxidative stress.Aims: The aim of this study was to undertake ex vivo assays for monitoring the disease in mice and increase our knowledge of the oxidative stress induced by tularemia.Methods: The mouse BALB/c model was chosen and the animals were infected by a dose 104 CFU of F. tularensis. After five days, the animals were euthanized. Blood immediately processed in plasma, spleen and liver were sampled from the cadavers. Oxidative stress markers, cytokines and histopathological were undertaken.Results: There was a significant link between oxidative stress and tularemia. Particularly elevated levels of malondialdehyde and decreased levels of low molecular weight antioxidants were found in the liver and spleen of tularemia-infected animals. The histopathological findings correlated well with the oxidative stress markers. The liver and spleen were proven to be significantly at risk from the disease and an association between stress and neutrophils in the affected organs was found. The histopathology excluded risk to other organs such as the kidney and or heart.Conclusions: Oxidative stress plays a significant role in tularemia infection in mice and this was confirmed by the histology.
Keywords: Francisella tularensis; intracellular pathogen; liver; spleen; reactive oxygen species; antioxidants